Non-Projected Visual Aids in the Teaching of General Science in Teachers' Colleges in Oyo State. - Oniye, Durogboye Oluwagbemileke (Obafemi Awolowo University, 2014)
This study focused on Non-projected Visual aids in the Teaching of General Science in Teachers' Colleges in Oyo State. The objectives of the study were the identification of available non-projected visual aids and their frequency of use in General Science teaching in the colleges. Others were to find out the problems faced by teachers in the use of non-projected visual aids for general science teaching and to identify the advantages teachers and students derive from the use of non-projected visual aids in teaching General Science. The research population consisted of all the general science students and teachers in all the then existing eighteen Grade Two Teachers' Colleges in Oyo State. The research sample consisted of four hundred and eight students and twenty General Science Teachers from twelve sampled Grade Two Teachers' Colleges. Data were collected with questionnaires.